A pharmacological study of Renshaw cell inhibition. - Curtis, D R (1976)
1. In cats anaesthetized with pentobarbitone a pharmacological investigation was made of the inhibition of Renshaw cells by dorsal root afferent volleys and ventral root antidromic volleys, and of the inhibition of motoneurones by Renshaw cells. 2. The effects of strychnine, bicuculline and tetanus toxin indicate that both glycine and GABA operate as inhibitory transmitters released on Renshaw cells by dorsal root volleys. 3. The 'mutual' inhibition of Renshaw cells, and the recurrent inhibition of motoneurones by Renshaw cells, are suppressed by strychnine: Renshaw cells are thus glycinergic inhibitory neurones, a proposal consistant with recent evidence for strychnine-sensitive inhibition of Ia interneurones by Renshaw cells. 4. The 'pause' which follows high frequency synaptic excitation of Renshaw cells is insensitive to strychnine, bicuculline and tetanus toxin, and is considered unlikely to be the consequence of synaptic inhibition.